Interrogation of EGFR Targeted Uptake of TiO(2) Nanoconjugates by X-ray Fluorescence Microscopy - Yuan, Ye (2011)
We are developing TiO(2) nanoconjugates that can be used as therapeutic and diagnostic agents. Nanoscale TiO(2) can be surface conjugated with various molecules and has the unique ability to induce the production of reactive oxygen species after radiation activation. One way to improve the potential clinical usefulness of TiO(2) nanoparticles is to control their delivery to malignant cells by targeting them to cancer cell specific antigens. Epidermal Growth Factor Receptor is one potential target that is enriched in epithelial cancers and is rapidly internalized after ligand binding. Hence, we have synthesized TiO(2) nanoparticles and functionalized them with a short EGFR binding peptide to create EGFR-targeted NCs. X-ray Fluorescence Microscopy was used to image nanoconjugates within EGFR positive HeLa cells. Further labeling of fixed cells with antibodies against EGFR and Protein A nanogold showed that TiO(2) nanoconjugates can colocalize with receptors at the cell’s plasma membrane. Interestingly, with increased incubation times, EGFR targeted nanoconjugates could also be found colocalized with EGFR within the cell nucleus. This suggests that EGFR-targeted nanoconjugates can bind the receptor at the cell membrane, which leads to the internalization of NC-receptor complexes and the subsequent transport of nanoconjugates into the nucleus.